2022
DOI: 10.1097/cm9.0000000000001937
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ulinastatin on the inflammatory response after video-assisted thoracic lobectomy in patients with lung cancer: a randomized controlled study

Abstract: Background:The first-line treatment for lung cancer is surgical resection, and one-lung ventilation (OLV) is the most basic anesthetic management method in lung surgery. During OLV, inflammatory cytokines are released in response to the lung tissue damage and promote local and contralateral lung damage through the systemic circulation. We designed a randomized, prospective study to evaluate the effect of the urinary trypsin inhibitor (UTI) ulinastatin on the inflammatory response after video-assisted thoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…UTI is a glycoprotein purified from healthy human urine 30 , 31 , 32 , 33 , 37 that inhibits the activity of protein hydrolases and consists of 143 amino acids with a relative molecular mass of approximately 67,000. UTI inhibits inflammatory responses and modulate immune function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UTI is a glycoprotein purified from healthy human urine 30 , 31 , 32 , 33 , 37 that inhibits the activity of protein hydrolases and consists of 143 amino acids with a relative molecular mass of approximately 67,000. UTI inhibits inflammatory responses and modulate immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown 29 , 30 , 31 that UTI effectively modulates inflammatory factor release, reduces endotoxic responses, and improves ischemia‐reperfusion injury of the microcirculation in the treatment of infectious diseases, such as severe pneumonia, severe pancreatitis, and sepsis, thereby reducing clinical morbidity and mortality, and is widely used in clinical practice in China, Korea, and Japan. 30 , 31 , 32 , 33 There are few reports involving UTI in the treatment of unliquefied PLA. This study aimed to retrospectively analyze the effectiveness of UTI in treating UPLA‐SS and provide a foundation for clinical application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation